Chants populaires arméniens - Chopanyan, Arshak 1872-1954; Brigham Young University (Paris P. Ollendorff, 1903)
Chants de d'amour -- Chants de danse et de fêtes -- Chants de mariage --Berceuses, chants d'enfant --Chants satiriques, badinages --Chants funbres -- Prières et poèmes religieux -- Chants historiques, contes -- Chants d'émigré -- Chants nationaux -- Chants divers.
Text only
Keywords: Songs, Armenian -- Texts -- Translations into French; Folk songs, Armenian -- Translations into French; Hymns, Armenian -- Translations into French; Patriotic songs, Armenian -- Translations into French; Armenian poetry -- Translations into French; Language and literature